Optimization of new eco-material synthesis obtained by phosphoric acid attack of natural Moroccan pozzolan using Box-Behnken Design. Issue 23 (1st December 2021) - Aziz, Ayoub; Driouich, Anas; Bellil, Abdelilah; Ali, Mohammed Ben; Mabtouti, Said E.L.; Felaous, Khadija; Achab, Mohammed; El Bouari, Abdeslam
Abstract: Natural pozzolan is a promising precursor for the synthesis of alkali-activated geopolymers. However, the acid activation of pozzolan is very poorly developed. In this respect, this paper presents an optimization study of the synthesis of geopolymers based on pozzolan and phosphoric acid using the Design Of Experiments (DOE) methodology. Indeed, a Box Behnken Design (BBD) associated with the Response Surface Methodology (RSM) is used. The analysis of variance ANOVA showed that the factors used for the modeling are significant in their sets. Thus, the study of the adjustment confirms the validation of the established models, by very high values of adjusted coefficient of determination (R 2 Adj-Cs = 95.63%, R 2 Ad-PWV = 95.73%, R 2 Adj-D = 97.62%, R 2 Adj-P = 98.24%, R 2 Adj-WA = 95.52%). Similarly, the RSM tool showed that the optimal conditions to elaborate a geopolymer with good physicomechanical properties (Compressive strength = 21.57 MPa, P-wave velocity = 2110 m/s, Density = 1.95 g/cm 3, Porosity = 12.8%, Water absorption = 6.06%) are as follows: Si/P = 1.25, H2 O/H3 PO4 = 2, and Li/So ratio = 0.9. Microstructural characterization of the optimal geopolymer by XRD and FTIR showed that the pozzolan is actively reacted with phosphoric acid, under the optimal conditions found by the Box Behnken Design model. This is revealed by the formation of a significant amount of amorphous phase, the formation of a new monetite-like mineral phase as well as the formation of Si–O–P bonds, which are the basis of the physicomechanical properties found.